Mimicking enzymatic systems: modulation of the performance of polymeric organocatalysts by ion-specific effects. Issue 16 (1st February 2016) - Xu, Yun; Hua, Zan; Zhang, Jian; Yang, Jun; Cao, Zhonglin; Zhang, Dongyang; He, Lingxin; J. Craig, Vincent S.; Zhang, Guangzhao; Liu, Guangming
Abstract : The performance of polymeric organocatalysts can be modulated by ion-specific effects based on the lessons learned from natural enzymatic systems. Abstract : Like natural enzymatic systems, our study has demonstrated that the activity of the polymeric organocatalysts can be modulated by ion-specific effects via the combination of anion-specific salting-in/out effects and anion-specific polarization of hydrogen bonding induced stabilization of the transition state.